PERCEPTIONS OF TEACHERS AND LEARNERS ON THE EFFECTIVENESS OF CIVIC EDUCATION IN THE DEVELOPMENT OF CIVIC COMPETENCY AMONG LEARNERS IN CHIPATA DISTRICT, ZAMBIA - Awoniyi Samuel Adebayo; Francis Lupupa Zimba (European Scientific Journal, ESJ, 2014)
The study examined the Perceptions of Teachers and Learners on the Effectiveness of Civic Education in the Development of Civic Competency among Learners in Chipata District, Eastern Province of Zambia. The study employed the descriptive quantitative method. The variables associated with the study were civic knowledge, civic skills and civic disposition. The total number of secondary schools in Chipata is seven (7) with 228 teachers and 7550 pupils.The sample comprised of three secondary schools (one single sex male, one single sex female and one co-educational). Thirty teachers (10 from each school) were selected randomly. One hundred and eighty(180) pupils (60 from each school and 20 from each of grade levels 10-12) were also selected using the simple random sampling technique. A selfconstructed structured questionnaire was used for data collection. The questionnaire was face and content validated. A pilot study was carried out in one co-education school in Chipata District using thirty five respondents (5 teachers and 30 pupils). The reliability of the instrument was determined using the Cronbach’s Alpha reliability method. An Alpha reliability coefficient of 0.829 was obtained. Data collected was analysed using the statistical package for Social Science (SPSS). Descriptive statistics was employed .The outcome of the analysis revealed that both teachers and pupils regard civic education as highly effective in the development of learner’ civic competency in terms of civic knowledge, civic skills and civic disposition. The findings of the study therefore revealed that civic education plays a significant role in the political development of the learner. Civic education is an important component of education that cultivates in learners to participate in public life of democracy, to use their rights and to discharge their responsibilities with the necessary knowledge and skills.